The Effects of a Context-Rich Approach in Teaching Thermodynamics - Mahmutović, Sabaheta; Mešić, Vanes (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Earlier research shows that at all educational levels students have many misconceptions about thermal phenomena. Often these misconceptions are related to difficulties with differentiating the meaning that concepts have in everyday language and in the language of science. In this study we aimed to investigate the effects of enriching traditional instruction about thermodynamics with qualitative and quantitative examples from everyday life. To that end we conducted a pre-post quasi-experiment with 114 high-school students (mostly 15-year-olds) divided into four subgroups. Two subgroups (n=60) received the traditional instruction, whereas in the remaining two subgroups (n=54) a context-rich approach to learning thermodynamics has been implemented. Analysis of covariance showed that there are no statistically significant between-group differences when it comes to conceptual understanding of thermodynamics. However, the context-rich approach proved to be significantly more effective when it comes to increasing students' interest in science. The level of aroused interest was higher in girls than in boys.